2020
DOI: 10.1186/s12955-020-01383-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Connor-Davidson Resilience Scale (CD-RISC) in a non-clinical population in Sweden

Abstract: Background: The Connor-Davidson Resilience Scale (CD-RISC) is the most widely used scale which assesses psychological resilience. Although it is recommended to be applied as a unidimensional scale, its factor structure, reliability, as well as discriminant and predictive validity need to be assessed when used in a new context. Moreover, the original five-factor structure has not been replicated in previous investigations. This study aimed to explore psychometric properties of the scale in a Swedish context. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 47 publications
(64 reference statements)
2
33
0
1
Order By: Relevance
“…For example, in a Sweden sample, the authors showed that the remaining model excluded 3 items, items 3 and 9 that form the "spiritual influences" from the initial model (Velickovic et al, 2020). Similar decisions were made by researchers from Australia and Spain, where their final model did not include all items from the original model (Burns & Anstey, 2010;González, Sierra, Martínez & Martinez-Molina, 2015).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, in a Sweden sample, the authors showed that the remaining model excluded 3 items, items 3 and 9 that form the "spiritual influences" from the initial model (Velickovic et al, 2020). Similar decisions were made by researchers from Australia and Spain, where their final model did not include all items from the original model (Burns & Anstey, 2010;González, Sierra, Martínez & Martinez-Molina, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…These results are in accordance with several studies of psychometric properties of CD-RISC 25. Some researches show that the factorial design of CD-RISC varies depending on the cultural context of the population studied (Ionescu, 2013) and the five-facture framework of CD-RISC 25 does not replicate in different contexts (Velickovic et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 12 , 13 , 20 , 21 Recently a Swedish population-based study has been published, where the mean score for psychological resilience was reported to 68.7 among women in a non-clinical population (N=1283, Cronbach´s alpha=0.92). 14 This non-clinical population was selected based on reaching out for people with lung- and heart diseases. Thus, Swedish norm data are not yet available.…”
Section: Methodsmentioning
confidence: 99%
“…4,6,[8][9][10][11] Higher levels of psychological resilience do not make the patients unaffected by distress, but they do help the patients to adapt when facing significant adversities. [12][13][14] In studies including BC patients, higher levels of psychological resilience have been found to be associated with higher levels of HRQoL. 4,8,10 The Connor-Davidson Resilience Scale 25 (CD-RISC25) is one of the resilience scales that has been demonstrated to have the best psychometric properties and is the most commonly and widely used resilience scale.…”
Section: Introductionmentioning
confidence: 99%